2021
DOI: 10.1007/s00248-021-01897-3
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Disturbance Linked with Host Microbiome Dispersion and Bd Dynamics in Temperate Amphibians

Abstract: Anthropogenic habitat disturbances can dramatically alter ecological community interactions, including host-pathogen dynamics. Recent work has highlighted the potential for habitat disturbances to alter hostassociated microbial communities, but the associations between anthropogenic disturbance, host microbiomes, and pathogens are unresolved. Amphibian skin microbial communities are particularly responsive to factors like temperature, physiochemistry, pathogen infection, and environmental microbial reservoirs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 78 publications
0
17
2
Order By: Relevance
“…This finding is contrary to those of other ranavirus studies, which have found ranavirus spread and prevalence to be coupled with human activity and urban environments [72][73][74]. The limited ranavirus prevalence in disturbed sites observed here is, however, consistent with other amphibian disease systems, such as Bd [33,75]. Given that ranavirus has broad host range in ectothermic vertebrates [76] and its prevalence has been shown to increase with amphibian and fish diversity [74], a potential driver for reduced disease prevalence in disturbed sites may therefore be fewer potential ranavirus carriers (in this case fish owing to already low endemic amphibian diversity).…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is contrary to those of other ranavirus studies, which have found ranavirus spread and prevalence to be coupled with human activity and urban environments [72][73][74]. The limited ranavirus prevalence in disturbed sites observed here is, however, consistent with other amphibian disease systems, such as Bd [33,75]. Given that ranavirus has broad host range in ectothermic vertebrates [76] and its prevalence has been shown to increase with amphibian and fish diversity [74], a potential driver for reduced disease prevalence in disturbed sites may therefore be fewer potential ranavirus carriers (in this case fish owing to already low endemic amphibian diversity).…”
Section: Discussioncontrasting
confidence: 99%
“…For example, habitat degradation (i.e. fragmentation and deforestation) can alter both skin and gut microbial communities of organisms by altering natural sources of microbial symbionts in the environment (Barelli et al ., 2015 ; Becker et al ., 2017 ; Hughey et al ., 2017 ; Jimenez et al ., 2020 ; Barnes et al ., 2021 ; Neely et al ., 2021 ). Similarly, exposure to human‐made chemicals in the environment has been shown to influence associations between hosts and microbial symbionts, in many cases resulting in negative effects to host health (Redford et al ., 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings indicate that habitat loss and fragmentation cause shifts in community composition of the amphibian microbiome, such as decreases in skin bacterial diversity (Becker et al ., 2017) and microbiome dysbiosis (Jiménez et al ., 2020; Neely et al ., 2022) in disturbed environments. Using methods to quantify the function (i.e.…”
Section: Potential Mechanisms Linking Habitat Split and Elements Of A...mentioning
confidence: 99%